FENOMENA KREATIF DUA PERUPA BALI DALAM MENGHADAPI MODERNISASI Kajian Proses Cipta Ketut Budiana dan Made Wianta Cerminan Transformasi Kultural Masyarakat Bali - Sari, Ni Made Purnama (Humanis, 2013)
In the process of changes in socio-cultural Bali, the presence of modernity is an inevitable thing. Some claim to modernity as a reference, objectives and even the road to progress,  both  in the  technical and practical ideas.  There  are  also points  out,  the emergence of modernity often offend traditional values of this island, which standardized through a series of conservation efforts. It also emerged in the works of Balinese art,  which has been in contact with modernity since the entry of outside painting techniques of artists such as Rudolf Bonnet, Walter Spies,  Arie Smith,  and  so  on.  With  reference  to  the process  of creation  and creativity of two artists of Bali,  Ketut  Budiana and Made Wianta,  this paper aims  to clarify the idea of these Balinese artists in the face of the process of changing the culture of Bali. Although both artists are trying to explore different visual art, the characteristics of  tradition has remained present in their creativity.  The trend of the creation of two artists, despite the attempt to achieve a universal modernity, but the views, thoughts and style of Balinese painting with full canvas, figurative iconic Bali, as well as the form of typical traditional way is also seen. It is suspected due to the influence of childhood each one  very  closely  with  the  Balinese  cultural  memory,  and  prove  that  even  though modernity tried to change many things in the present life, the basic characteristics of the tradition will not disappear, which actually can be developed into a form of awareness of the importance of maintaining the value locality for the preservation of cultural heritage of Bali.
Keywords: Tradition, modernity, process of changes